French Lessons in Late-Medieval England : The Liber Donati and Commune Parlance. - Critten, Rory G. (Foundations - ARC Series, 2023)
These teaching and reference materials paint a vivid picture of the kinds of French that medieval English learners might desire to wield and of the high levels of fluency they could achieve.